Atraumatic Isolated Bilateral Fibular Shaft Fragility Fracture: a Rare Case - kalluraya, DR Suryakanth; Hosangadi, Adiveppa; Munavalli, Prabhu; Kumar, Akash (Scripta Medica, 2023)
Fragility fractures, a form of stress fracture brought on by physiological stress on weak bones are not common. It might be challenging to diagnose a fragility fracture, since a standard X-ray shows signs of fracture repair rather than the actual fracture. Here is presented a case of a young woman who has been complaining of pain in both legs for 4 months and has been unable to stand for 1 week. A further analysis revealed that patient’s vitamin D levels were insufficient.